(untitled) (Anclajes, 2020)
In Chicas muertas (2014) –published prior to the #NiUnaMenos movement– Selva Almada (1973) tells the story of the unpunished femicides of three young women from various locations in Argentina during the 1980s, a time coinciding with the restoration of democracy after the last military dictatorship. Almada uses non-fiction to present the sociopolitical and media context in which Andrea Danne (Entre Ríos), María Luisa Quevedo (Chaco) and Sara Mundín (Córdoba) were murdered. Using Cristina Rivera Garza’s framework of necrowriting and a “poetics of disappropiation” to narrate these cases, Almada, as if opening a file, exposes the growing number of gender-motivated crimes that have occurred up until our time.